DECISION SUPPORT SYSTEM UNTUK PROPERTI PREMIUM: INTEGRASI AHP DAN TOPSIS DALAM MENGANALISIS PROPERTI SINAR MAS GROUP - Aldo Putra Ramaddan; M. Ramaddan Julianti; Nunung Nurmaesah (Universitas Teknokrat Indonesia, 2025)
Implementation of decision support system (dss) to select the best premium property from sinar mas group in bsd city. the main problem is the complexity of decision making in the premium property segment involving various criteria such as price, location, facilities, land area, and investment potential. the aim of this study is to develop a dss that integrates the analytical hierarchy process (ahp) method to determine criteria weights and the technique for order preference by similarity to ideal solution (topsis) to rank property alternatives based on proximity to the ideal solution. the research methods include criteria identification, data collection, criteria weight calculation using ahp, normalization and preference value calculation using topsis, and result evaluation. the results show that the elyon property type is the best alternative with the highest preference value of 0.74112, followed by adora primes and terravia belova. this study demonstrates the effectiveness of integrating ahp and topsis in providing objective and measurable decision recommendations for premium property purchases. this system is expected to assist prospective buyers, developers, and property consultants in making better decisions and has the potential to be developed into a digital application.